Association of maternal autoimmune disease and early childhood infections with offspring autism spectrum disorder: A population‐based cohort study. Issue 12 (3rd October 2022) - Nielsen, Timothy C.; Nassar, Natasha; Shand, Antonia W.; Jones, Hannah F.; Han, Velda X.; Patel, Shrujna; Guastella, Adam J.; Dale, Russell C.; Lain, Samantha J.
Abstract: The aim of this study was to examine potential synergistic effects between maternal autoimmune disease and early childhood infections and their association with autism spectrum disorder (ASD) in offspring. Both exposures have been associated with increased risk of ASD in previous studies, but potential synergistic effects remain underexplored. We conducted a population‐based cohort study of singleton children born at term gestation (37–41 weeks) in New South Wales, Australia from January 2002 to December 2008. Maternal autoimmune diagnoses and childhood infections before age 2 years were identified from linked maternal and child hospital admissions, and ASD diagnoses by age 9 years were identified from linked disability services data. Multivariable logistic regression assessed the association between each exposure and ASD and additive interaction between exposures, controlling for potential confounders. A total of 18, 451 children exposed to maternal autoimmune disease were propensity score matched (1:2) to 36, 902 unexposed children. Any maternal autoimmune disease (adjusted odds ratio (aOR) 1.25, 95% confidence interval (CI) 1.07–1.47) and any childhood infection before age 2 years (aOR 1.38, 95% CI 1.15–1.67) were each associated with ASD. However, there was no evidence of additive interaction between the two exposures (relative excess risk due to interaction [RERI] 0.128, 95% CI ‐0.418‐0.675) resulting in increased odds of ASD in offspring. Future studies could examine potential interactions between other sources of maternal immune activation and childhood infection and impact on ASD and other neurodevelopmental disorders. Lay Summary: Inflammation during pregnancy and in early childhood may influence how a child's brain develops, increasing the risk of autism spectrum disorder (ASD). In this study, we found that having a mother with an autoimmune disease and being admitted to hospital with an infection before age two each increased a child's odds of ASD. However, children with maternal autoimmune disease and an infection did not experience any additional increase in risk from having both exposures together.